1997
DOI: 10.3109/00365529708996540
|View full text |Cite
|
Sign up to set email alerts
|

A Multiplex Polymerase Chain Reaction Assay for the Detection of Mycobacterium paratuberculosis DNA in Crohn's Disease Tissue

Abstract: The present MPCR method is highly specific and can detect M. paratuberculosis DNA more reliably. These findings do not support an aetiologic role of M. paratuberculosis in Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Many studies probing for the IS900 gene sequence of M. avium in intestinal tissue have been conducted to date. The results of most of these studies have been negative (1,6,7,10,15,30,32; S. W. P. Wu, C. C. Pao, J. Chan, and T. S. B. Yen, Letter, Lancet 337:174-175, 1991) or similarly positive for cases and controls (36).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies probing for the IS900 gene sequence of M. avium in intestinal tissue have been conducted to date. The results of most of these studies have been negative (1,6,7,10,15,30,32; S. W. P. Wu, C. C. Pao, J. Chan, and T. S. B. Yen, Letter, Lancet 337:174-175, 1991) or similarly positive for cases and controls (36).…”
Section: Discussionmentioning
confidence: 99%
“…Case series 1–4 , 13 , 14 and case‐control 5–12 , 15–19 studies have reported conflicting results regarding the possibility that Crohn’s disease is caused by a mycobacterial infection. If an infection is the cause of disease, effective antimicrobial treatment may be associated with clinical improvement and a change in the natural history of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Humoral immune response to mycobacterial antigens was also used to support a relationship between Crohn’s disease and mycobacterial infection 9 , . 10 However, other studies relying on culture, 11 , 12 polymerase chain reaction 11–16 and measurement of specific immune responses 17–19 have not supported an aetiologic relationship between mycobacteria and Crohn’s disease.…”
Section: Introductionmentioning
confidence: 99%
“…4,6,7,9,15,16,19 Other authors have found a variable number of cases, up to 100%, to harbor the organism. 1,3,5,8,[10][11][12][13][14]18 Several reasons may be responsible for the variability in these results.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] However, if MAP and Crohn's disease are etiologically related, then intuitively the granulomas that are characteristic of the latter should harbor the organism. Indeed, some authors have associated the ability to identify MAP DNA with the presence of granulomas, 1,2 while others have not.…”
mentioning
confidence: 99%